1988
DOI: 10.1002/tea.3660250607
|View full text |Cite
|
Sign up to set email alerts
|

Predicting course performance in freshman and sophomore physics courses: Women are more predictable than men

Abstract: This study investigated the extent to which thinking skills and mathematical competency would predict the course performance of freshman and sophomore science majors enrolled in physics courses. Multiple-regression equations revealed that algebra and critical thinking skills were the best overall predictors across several physics courses. Although arithmetic skills, math anxiety, and primary mental abilities scores also correlated with performance, they were redundant with the algebra and critical thinking. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Firstly, separate group analyses were conducted for each group to establish a baseline model of academic success in the groups, following the procedure recommended by Bryne (1998). It was anticipated that the model would not change across groups, but that some parameter estimates might vary across groups, based on previous research, which suggested that some differences in the strength of the relationship between variables may be detected depending on the gender or age of the student (Eppler & Harju, 1997;McCammon et al, 1988;Murray-Harvey, 1993;Nunn, 1994;Summerfield & Youngman, 1999).…”
Section: Multigroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, separate group analyses were conducted for each group to establish a baseline model of academic success in the groups, following the procedure recommended by Bryne (1998). It was anticipated that the model would not change across groups, but that some parameter estimates might vary across groups, based on previous research, which suggested that some differences in the strength of the relationship between variables may be detected depending on the gender or age of the student (Eppler & Harju, 1997;McCammon et al, 1988;Murray-Harvey, 1993;Nunn, 1994;Summerfield & Youngman, 1999).…”
Section: Multigroup Analysesmentioning
confidence: 99%
“…Adult Learning Australia (2002) reported that, between 1990 and 2000, mature-age student participation in university increased by 52%. Previous research had found that mature-age students, compared to younger students, have different views of themselves as learners (Nunn, 1994;Summerfield & Youngman, 1999), approach the task of learning differently (Murray-Harvey, 1993), have different achievement-related characteristics (i.e., locus of control) (Eppler & Harju, 1997;Nunn, 1994), and their ability to predict performance differs across groups (McCammon, Golden, & Wuensch, 1988). Power, Robertson, and Baker (1987) demonstrated that previous performance was not as accurate a predictor for mature-age students' performance as it was for school leavers' performance.…”
Section: Introductionmentioning
confidence: 97%
“…Researchers have found critical thinking skills predictive of per formance in a variety of college courses, such as physics and psy chology (Gadzella, Ginther, & Bryant, 1997;McCammon, Golden, & Wuensch, 1988). Nonetheless, critical thinking may be more strongly related to some course measures than to others.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the A grade students made more accurate inferences, deductions, and interpretations of the information they studied. In the study reported by McCammon, et al (1988) on freshman and sophomore science majors who were enrolled m physics, the authors also reported that critical thinlung was one of the best predictors.…”
Section: Discussionmentioning
confidence: 97%